2005
DOI: 10.1097/01.wnr.0000179078.54906.52
|View full text |Cite
|
Sign up to set email alerts
|

Lithium attenuates stress-induced impairment of long-term potentiation induction

Abstract: Stress impairs the induction of long-term potentiation in the hippocampus as well as hippocampus-dependent memory. Lithium, a classical mood stabilizer, is known to have bene¢cial e¡ects on stress-induced impairment of spatial memory. In the present study, we investigated lithium e¡ects on the impairment of long-term potentiation induction after exposure to acute immobilization stress. As previously reported, immobilization stress impaired long-term potentiation induction in the CA1region of rat hippocampal sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Lithium treatment inhibited learning, memory and speed of information processing in patients with bipolar disorders and to some extent in control subjects (Kocsis et al, 1993;Honig et al, 1999;Stip et al, 2000;Pachet and Wisniewski, 2003). Lithium, however, was also reported to enhance memory in some tasks (Tsaltas et al, 2007), or to attenuate memory impairments induced by other factors (Lim et al, 2005). Although it has been shown that lithium can regulate signal transduction pathways in several regions of the brain, and alter the function of several neurotransmitter systems (Branisteanu and Volle, 1975;Manji et al, 1995), the definitive mechanism(s) for the drugs effects has not been established.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Lithium treatment inhibited learning, memory and speed of information processing in patients with bipolar disorders and to some extent in control subjects (Kocsis et al, 1993;Honig et al, 1999;Stip et al, 2000;Pachet and Wisniewski, 2003). Lithium, however, was also reported to enhance memory in some tasks (Tsaltas et al, 2007), or to attenuate memory impairments induced by other factors (Lim et al, 2005). Although it has been shown that lithium can regulate signal transduction pathways in several regions of the brain, and alter the function of several neurotransmitter systems (Branisteanu and Volle, 1975;Manji et al, 1995), the definitive mechanism(s) for the drugs effects has not been established.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, the effects of lithium on memory may suggest a state dependency. It has been also shown that lithium attenuates stress-induced memory impairment (Lim et al, 2005). An alternate explanation is that the effects on memory retrieval of a drug given before the retention test simply depend on how well the information has been stored previously.…”
Section: +++mentioning
confidence: 98%
“…Electrophysiologically, chronic lithium increases long-term potentiation (LTP) in hippocampal neurons (Shim et al . 2007) and alleviates stress-induced LTP impairment (Lim et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that acute immobilization stress impaired LTP induction in the CA1 region, which was restored by addition of lithium of therapeutic concentration to artificial CSF in brain slices. However, the addition of lithium to slices from non-stressed animals had no effect (Lim et al, 2005).…”
Section: The Effect Of Mood Stabilizers On Stress-induced Impairmentsmentioning
confidence: 99%